2010
DOI: 10.1186/1476-511x-9-62
|View full text |Cite
|
Sign up to set email alerts
|

Membrane plasmalogen composition and cellular cholesterol regulation: a structure activity study

Abstract: BackgroundDisrupted cholesterol regulation leading to increased circulating and membrane cholesterol levels is implicated in many age-related chronic diseases such as cardiovascular disease (CVD), Alzheimer's disease (AD), and cancer. In vitro and ex vivo cellular plasmalogen deficiency models have been shown to exhibit impaired intra- and extra-cellular processing of cholesterol. Furthermore, depleted brain plasmalogens have been implicated in AD and serum plasmalogen deficiencies have been linked to AD, CVD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 66 publications
3
47
1
Order By: Relevance
“…In addition, phospholipids have also been suggested to play important roles in HDL-mediated RCT (39)(40)(41)(42). Interestingly, Pls-defi cient cells have been shown to exhibit reduced cholesterol effl ux by HDL ( 43 ), which may be associated with impaired cellular processing of cholesterol ( 44,45 ). These notions suggest the relevance of serum Pls to the physiologically important functions of HDL, including RCT.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, phospholipids have also been suggested to play important roles in HDL-mediated RCT (39)(40)(41)(42). Interestingly, Pls-defi cient cells have been shown to exhibit reduced cholesterol effl ux by HDL ( 43 ), which may be associated with impaired cellular processing of cholesterol ( 44,45 ). These notions suggest the relevance of serum Pls to the physiologically important functions of HDL, including RCT.…”
Section: Discussionmentioning
confidence: 97%
“…Alkenylphosphatidylethanolamines (plasmalogens) contain a vinyl ether linkage that is particularly susceptible to oxidation by reactive oxygen species, and as such they are proposed to play an antioxidant role in membranes and lipoproteins [24]. Ethanolamine plasmalogens prevent oxidation of cholesterol by reducing its oxidisability in phospholipid bilayers [25] and are involved in the regulation of cholesterol esterification and efflux [26]. We have previously observed that some plasmalogen species are negatively associated with conditions of high oxidative stress, including type 2 diabetes [16] and coronary artery disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmalogen deficiency causes the impaired highdensity lipoprotein (HDL)-mediated cholesterol efflux from murine macrophage-like cells (67), the altered transport of internalized cholesterol to the endoplasmic reticulum (3), and abnormal cellular distribution of cholesterol (68). Moreover, addition of cis-(Ϯ)-2-O-docosahexaenoyl-1-O-hexadecylglycerol increases cholesterol esterification by raising the sterol-Oacyltransferase 1 expression level in HEK293 cells (69) and elevation of plasmalogens reduces the cholesterol level in HeLa cells cultured in the presence of exogenously added cholesterol (Fig. 4F).…”
Section: ) By Enhancing March6-mediated Ubiquitination (32)mentioning
confidence: 99%